Theoretical and numerical simulation study on heat and mass transfer mechanism of GM refrigerator cryopump - Jiaqi Lang; Xiuping Zhang; Rujin Wang (AIP Advances)
The cryopump relies on the cryocondensation mechanism to create a clean, high-vacuum environment. Studying the heat and mass transfer mechanism and enhancing the performance of the cryopump are important because its heat and mass transfer performance directly affects the quality of the vacuum environment. This study proposes a systematic method for analyzing the mechanism influencing spatial changes, particle motion characteristics, and heat and mass transfer. This study identifies the key factors affecting the heat and mass transfer and investigates the influence of various factors in the vacuum chamber, liquid-nitrogen cooling area, and liquid-helium cooling area on the mass transfer performance. Next, the main source of heat load and the influence of spatial layout on the heat load are determined and a method for reducing the heat load is introduced. A cryopump designed based on these conclusions delivered a 33% higher pumping speed, a 35% shorter cooling time, and a better vacuum performance than the traditional cryopump in a simulation analysis. This study can provide guidance for the development of advanced cryopumps and instruct the design and operation of cryovacuum systems.